1999
DOI: 10.1159/000020924
|View full text |Cite
|
Sign up to set email alerts
|

Low Neonatal Risk of Thrombocytopenia in Pregnancy Associated with Immune Thrombocytopenic Purpura

Abstract: Objective: To estimate the risk of neonatal thrombocytopenia in infants born to mothers with immune thrombocytopenic purpura (ITP). Methods: During the years 1993–1997, there were 6,082 deliveries. There were 32 infants born to 31 mothers with ITP. Cordocentesis was performed between 34 and 41 weeks of gestation in 16 mothers with ITP. The cord blood platelet count was checked in all cases at delivery. Results: In mothers with ITP, 5 neonates (15.6%) had mild thrombocytopenia and 7 neonates (21.9%) moderate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Severe thrombocytopenia in the newborn can cause hemorrhagic manifestations, the most dangerous of which is intracranial hemorrhage. In our cohort, thrombocytopenia was observed in 19.7% of neonates, which is similar to rates previously described [ 4 , 5 , 6 , 7 , 8 ]. Although its incidence is relatively low, intracranial bleeding is a serious thrombocytopenia complication in neonates born to mothers with ITP [ 4 , 5 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Severe thrombocytopenia in the newborn can cause hemorrhagic manifestations, the most dangerous of which is intracranial hemorrhage. In our cohort, thrombocytopenia was observed in 19.7% of neonates, which is similar to rates previously described [ 4 , 5 , 6 , 7 , 8 ]. Although its incidence is relatively low, intracranial bleeding is a serious thrombocytopenia complication in neonates born to mothers with ITP [ 4 , 5 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our series, only two of the offspring of the five mothers with chronic ITP suffered TP, an incidence of 40% which is in concordance with other reports [14][15][16]. It was also observed that of the two neonates who suffered in relation to maternal ITP, only one was associated with TP in the mother.…”
Section: Discussionsupporting
confidence: 92%
“…Despite low maternal platelet count, fetal intracranial haemorrhage is very rare. Hence, the mode of delivery in these patients can be determined mainly by obstetric indications (Song et al 1999;Payne et al 1997).…”
Section: Discussionmentioning
confidence: 99%